2015
DOI: 10.1186/s12917-015-0553-z
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the prevalence of Salmonella in dogs within the Midlands region of the United Kingdom

Abstract: Background: The intimate relationship between dogs and their owners has the potential to increase the risk of human exposure to bacterial pathogens. Over the past 40 years, there have been several reports on transmission of salmonellae from dogs to humans. This study therefore aimed to determine the prevalence of Salmonella in the faeces of dogs from the Midlands region of the United Kingdom to assess exposure risk and potential for zoonotic transmission. Results: A total of 436 apparently healthy dogs without… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
47
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(69 citation statements)
references
References 44 publications
6
47
3
Order By: Relevance
“…Similarly, prevalence in dogs in Iran (13.2%), was comparable to the current finding [2]. However, studies in some developed countries showed much lower rates of Salmonella carriage compared to the present finding, for example, 0% in Canada [17]; 0.2% in UK [18], 1% in Turkey [19], and 2.3% in Colorado, USA [20]. The possible reason for the high prevalence of Salmonella in the current study and other previous studies compared to the ones conducted in developed countries could be due to differences in pet sanitary practices, feeding habit, difference in public awareness about dog zoonosis and socioeconomic status of the owners.…”
Section: Discussionsupporting
confidence: 86%
“…Similarly, prevalence in dogs in Iran (13.2%), was comparable to the current finding [2]. However, studies in some developed countries showed much lower rates of Salmonella carriage compared to the present finding, for example, 0% in Canada [17]; 0.2% in UK [18], 1% in Turkey [19], and 2.3% in Colorado, USA [20]. The possible reason for the high prevalence of Salmonella in the current study and other previous studies compared to the ones conducted in developed countries could be due to differences in pet sanitary practices, feeding habit, difference in public awareness about dog zoonosis and socioeconomic status of the owners.…”
Section: Discussionsupporting
confidence: 86%
“…It has been used as an effective antibacterial agent against most of pathogenic bacterial species in animals including Salmonella, Escherichia coli, Pasturella and Staphylococcus species 6, 7 . Dogs are generally considered to more likely to these type of bacterial infections 8, 9 . Considering its exceptional safety as well as efficacy, Cyx might be a promising antibacterial agent to treat infectious diseases in various animal species, including canines.…”
Section: Introductionmentioning
confidence: 99%
“…in dogs, regardless of diet, is suspected to be low but estimates up to 18.0% in clinically normal dogs have been documented Lowden et al, 2015). This notion is consistent with data obtained from our study with less than 5.6% of total fecal samples (n=36) testing positive for Salmonella spp.…”
Section: Microbial Presencesupporting
confidence: 92%